Short Review on the Origin and Countermeasure of Biomass Slagging in Grate Furnace - Zhu, Yiming; Niu, Yanqing; Tan, Houzhang; Wang, Xuebin (Frontiers in Energy Research, 2014)
Given the increasing demand for energy consumption, biomass has been more and more important as a new type of clean renewable energy source. Biomass direct firing is the most mature and promising utilization method to date, while it allows a timely solution to slagging problems. Alkali metal elements in the biomass fuel and the ash fusion behavior, as the two major origins contributing to slagging during biomass combustion, are analyzed in this paper. The slag presents various layered structures affected by the different compositions of ash particles. Besides, the high-temperature molten material which provides a supporting effect on the skeletal structure in biomass ash was proposed to evaluate the ash fusion characteristics. In addition, numerous solutions to biomass slagging, such as additives, fuel pretreatment and biomass co-firing, were also discussed.